Regional unemployment in Poland: A legacy of central planning - Patrick Paul Walsh (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 2000)
We model job reallocation and unemployment as outcomes jointly determined by the structure of inherited social capital within a two-sector Optimal Speed of Transition model. Treating regions of Poland as independent labour markets, the socio-economic inheritance of regions is found to be a legacy of planning that determines regional job reallocation rates. In turn, higher rates of (instrumented) regional job reallocation is shown to boost regional unemployment turnover, reduce the duration of frictional and increase the incidence of structural unemployment. At the regional level, the benefit system facilitates the job reallocation process and accumulates out-of-date human capital.
Keywords: J6; L0; O5; 330; Social Capital; Job Reallocation; Regional Unemployment and Poland; Dynamic Computable General Equilibrium Model